Determination of antibody levels in egg-yolks from laying hens vaccinated against Newcastle disease - SINGH, GURKIRPAL (The Indian Journal of Animal Sciences, 2013)
Egg-yolks from commercial poultry farms/flocks collected at intervals following various schedules of Newcastle disease (ND) vaccination were tested for ND antibody levels by the haemagglutination inhibition (III) test. G.M. antibody titres ranged from 2.5 to 32.0. The antibodies wefe detected at moderate to high levels at 4-21 weeks after the last booster dose with R2B strain vaccine. The persistence of antibodies was however atlow levels at 35-43 weeks. HI antibody titres in both yolk and serum taken from the same chicken 16/43 weeks, Or from different hens 4 weeks after the booster dose were similar. The wide variation of antibody titres appeared to be due to different intervals between collection of eggs ami the last booster vaccination. different vaccination regimens followed and other factors. Apparently. there is a need 10 follow unifonn vaccination schedules against ND in poultry breeding establishments and poultry farms.